EFFECT OF ANTIBIOTICS AND PROBIOTICS ON POULTRY SALMONELLOSIS - Ortikov T.Z (TADQIQOTLAR.UZ, 2024)
This article presents the results of a study of the antibiotic and probiotic susceptibility of Salmonella enteritidis and Salmonella typhimurium, the causative agents of salmonellosis in chickens. As a result of laboratory studies, the causative agents of poultry salmonellosis were found to be Salmonella enteritidis and Salmonella typhimurium are sensitive to antibiotics such as Ciprox, Baytril, Levomycetin and also showed high sensitivity to the probiotic ’Innoprovet’, which can be further used for the treatment of poultry salmonellosis caused by Salmonella enteritidis and Salmonella typhimurium.